Dobrava hantavirus variants found in Apodemus flavicollis mice in Kırklareli Province, Turkey. Issue 5 (13th February 2018) - Polat, Ceylan; Sironen, Tarja; Plyusnina, Angelina; Karatas, Ahmet; Sozen, Mustafa; Matur, Ferhat; Vapalahti, Olli; Oktem, I. Mehmet Ali; Plyusnin, Alexander
Abstract : Hantaviruses infect humans via inhalation of viral particles within secretions of infected rodents or rarely through direct contact with infected rodents. Determining the prevalence of hantavirus infections among rodent populations is of vital importance to obtain information on hantavirus‐related cases and to predict possible outbreaks. We hypothesized that DOBV strains circulating in the Thrace Region in Turkey would be related to other Balkan DOBV strains. In this study, hantavirus infections in the rodent population of the Kırklareli‐İğneada Region (north‐western Turkey, near the Bulgarian border) were investigated. This region is of particular importance, as it is located in the south‐eastern margin of the European continent and was used as an entrance point of Asian faunal elements into Europe. DOBV infection was detected in eight of 73 rodents; all were of the Apodemus flavicollis species. Partial sequences of the viral S‐, M‐, and L‐genome segments were recovered and compared with previously reported DOBV sequences. The newly characterized Turkish strains were similar to other DOBV variants. Silent nucleotide mutations were dominant. The hantavirus prevalence in the İğneada region was similar to what has been reported in Greece and Bulgaria. For the first time, the M‐segment sequences of DOBV from Turkey were recovered and genetic data of hantaviruses from Thrace region of Turkey were obtained.